Liliana solved the equation below. When she tried to verify her answer, she realized she made an error.
![Liliana solved the equation below When she tried to verify her answer she realized she made an error class=](https://us-static.z-dn.net/files/d5b/279549cf6c175b13ff3cf3f88dd0d976.png)
![Liliana solved the equation below When she tried to verify her answer she realized she made an error class=](https://us-static.z-dn.net/files/d17/bc71bcff28891707da1c365b3f00b1b5.png)
Answer:
(B)
Step-by-step explanation:
The given expression is:
[tex]\frac{1}{3}(x+18)=7[/tex]
Upon solving the above expression, we get
[tex]\frac{1}{3}(x+18)=7[/tex]
Step 1. Solving the above equation, we get
[tex]\frac{1}{3}x+6=7[/tex]
Step 2. Subtracting 6 on both the sides of the above equation, we have
[tex]\frac{1}{3}x+6-6=7-6[/tex]
Step 3. The equation can be written as:
[tex]\frac{1}{3}x=1[/tex]
Step 4. Cross multiplying the above equation , we have
[tex]x=3[/tex]
She made an error in step 2 as she added 6 on right hand side but in actual we have to subtract 6 on that side.
Thus, option (B) is correct.